Analysis on the Seasonal Variations in Carrageenans of Hypnea flagelliformis and Sarconema filiforme by FTIR Spectroscopy - RAJASULOCHANA, N.; GUNASEKARAN, S. (Asian Journal of Chemistry, 2010)
Carrageenans are the most common and abundant cell wall polysaccharides of red algaeand are commercially important sulphated galactans. In the present study, polysaccharides extracted from Hypnea flagelliformis and Sarconema filiforme of summer and winter collections, were examined by FTIR spectroscopic analysis. The spectra of Hypnea flagelliformis collected in both seasons are correspondingly similar to that of kappa carrageenan. FTIR spectra of Sarconemea filiforme showed a peak at 805 cm-1 which confirms the presence of 3,6-anhydro galactose-2-sulphate. This is characteristic of iota carrageenan. The seasonal variations occur in the absorption bands of polysaccharides.